A new clinical classification and treatment strategies for temporomandibular joint ankylosis. Issue 11 (November 2020) - Bi, R.; Jiang, N.; Yin, Q.; Chen, H.; Liu, J.; Zhu, S.
Abstract: Temporomandibular joint ankylosis (TMJA) is a complicated condition that affects not only the condyle, but also the maxillofacial complex. Thus, it is often challenging to find a standardized treatment strategy for TMJA. This study was performed to analyse our experience with 95 TMJA patients over a 4-year period and develop a new classification system ('CDA'). The CDA classification system divides TMJA patients into eight different groups according to the preservability of the condyle (C), severity of the dentofacial bone deformity (D), and skeletal age (A). The 95 patients (129 ankylosed joints) were treated using different strategies based on this CDA classification. Treatment options included preserving or reconstructing the condylar head, surgical correction of jaw deformities, and close follow-up of mandibular growth. After treatment, all 129 ankylosed joints were completely released and the average maximum inter-incisal opening (MIO) increased from 3.6 ± 3.2 mm to 32.8 ± 5.4 mm, with no recurrence of ankylosis found during follow-up. In conclusion, this new CDA classification can effectively guide treatment strategies for TMJA patients. Using particular strategies for patients based on specific CDA classifications could provide optimal management to the benefit of TMJA patients.